2018
DOI: 10.1016/j.surg.2017.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cyst fluid glucose: rapid, inexpensive, and accurate diagnosis of mucinous pancreatic cysts

Abstract: Cyst fluid glucose has significant advantages over carcinoembryonic antigen and should be considered for use as a routine diagnostic test for pancreatic mucinous cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 27 publications
2
55
0
1
Order By: Relevance
“…There has been an interest in using cyst fluid glucose levels to differentiate IPMNs and MCNs from other types of cysts [28,29]. A recent study evaluated this in 153 patients all of whom had undergone surgical resection [30]. Using a cutoff of ≤50 mg/dl, cyst fluid glucose had 92% sensitivity and 87% specificity for identifying IPMNs and MCNs from other cyst types, and had a higher accuracy of 90 versus 69% compared with cyst fluid CEA [30].…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%
“…There has been an interest in using cyst fluid glucose levels to differentiate IPMNs and MCNs from other types of cysts [28,29]. A recent study evaluated this in 153 patients all of whom had undergone surgical resection [30]. Using a cutoff of ≤50 mg/dl, cyst fluid glucose had 92% sensitivity and 87% specificity for identifying IPMNs and MCNs from other cyst types, and had a higher accuracy of 90 versus 69% compared with cyst fluid CEA [30].…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%
“…Wu et al demonstrated 98% sensitivity and 100% specificity in diagnosing IPMN when testing cyst fluid [35]. Other single markers, such as glucose and neutrophil gelatinase-associated lipocalin (NGAL), have also been investigated with no ability to stratify IPMN [36][37][38]. Fortunately, there are now several single markers with the ability to both identify and grade IPMN dysplasia.…”
Section: Amylase < 250mentioning
confidence: 99%
“…Glucose in cyst fluid is a proposed new biomarker of interest for non-mucinous cystic lesions. Preliminary data are promising, yet its application is still investigational [81].…”
Section: Biochemical Markersmentioning
confidence: 99%